If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -24 = 2(u + -5) + -4u Reorder the terms: -24 = 2(-5 + u) + -4u -24 = (-5 * 2 + u * 2) + -4u -24 = (-10 + 2u) + -4u Combine like terms: 2u + -4u = -2u -24 = -10 + -2u Solving -24 = -10 + -2u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '2u' to each side of the equation. -24 + 2u = -10 + -2u + 2u Combine like terms: -2u + 2u = 0 -24 + 2u = -10 + 0 -24 + 2u = -10 Add '24' to each side of the equation. -24 + 24 + 2u = -10 + 24 Combine like terms: -24 + 24 = 0 0 + 2u = -10 + 24 2u = -10 + 24 Combine like terms: -10 + 24 = 14 2u = 14 Divide each side by '2'. u = 7 Simplifying u = 7
| (x+3)(x+4)-(9x^2+7)=5 | | -12=5y+8(y+5) | | 4(6.36363636364)=25.45454545 | | 14+24= | | Raizdex-5=3x | | 4(6.36)=x | | d/5 | | 569.7216=2*3.14r^2+2*3.14r*17.4 | | 3.50x+x=7020 | | A=by+cx+d | | 4(6.36363636364)=x | | 12x=18*1/3x | | 5/7m=-55 | | 18*1/3x | | 3.5x-x=7020 | | 18*x/3x | | x^2+10x+16=14 | | 8*x/3x | | 10y+5=5 | | 5s-s=260 | | 14+5=(-5)x-6(-3x+15)+5 | | 6x+3y-2z+w=12 | | 3x-13+5=10 | | 7m^4*2m^3= | | 5+[1+2(2x-3)]=6(x+5) | | 6r*2r^3= | | -7(1+6x)=455 | | 6(-1x+1)=-24 | | 6x-6/3 | | 5-(x-4)=6x-5 | | -6(-5+5x)=-120 | | y^2+29=33 |